PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP INDEKS HARGA SAHAM GABUNGAN INDONESIA 2017-2022 - Prasetya, Nadila Azza Nur; Moh. Athoillah (Contemporary Studies in Economic, Finance and Banking, 2023)
The more integrated the global economy is, the more the capital market will respond to currently available domestic and global information as a form of consideration in making investment decisions. Investment decisions generally consider a number of internal and external factors. The purpose of this study is to analyze whether the Non-Farm Payroll (NFP), FED Rate, BI Rate, and Dow Jones Index partially and simultaneously have a significant effect on the Indonesian Composite Stock Index (IHSG) in 2017:1-2022:12. The data in this study used secondary data using the time series multiple linear regression analysis method using the E-views version 10 application. The results showed that the NFP, FED Rate, BI Rate, and the Dow Jones index had simultaneous effect on the IHSG. The FED Rate, BI Rate, and Dow Jones Index variables have a significant positive effect on the IHSG, while the NFP variables has no significant effect on the IHSG.